Secondary metabolites as potential drug candidates against Zika virus, an emerging looming human threat: Current landscape, molecular mechanism and challenges ahead - Nabeelah Bibi Sadeer; Chaker El Kalamouni; Asaad Khalid; Ashraf N. Abdalla; Gokhan Zengin; Le Van Khoa Bao; Mohamad Fawzi Mahomoodally (Elsevier, 2023)
Nature has given us yet another wild card in the form of Zika virus (ZIKV). It was found in 1947, but has only recently become an important public health risk, predominantly to pregnant women and their unborn offspring. Currently, no specific therapeutic agent exists for ZIKV and treatment is mainly supportive. Natural products (NPs) can serve as a major source of potent antiviral drugs. To create this review, a comprehensive search was conducted from different databases (PubMed, ScienceDirect, Google scholar). A statistical analysis on the number of publications related to NPs and ZIKV was conducted to analyse the trend in research covering the period 1980-2020. From the data collated in this review, a number of NPs have been found to be inhibitive towards different stages of the ZIKV lifecycle in in vitro studies. For instance, baicalin, (-)-epigallocatechin gallate, curcumin, nanchangmycin, gossypol, cephaeline, emetine, resveratrol, berberine, amongst others, can prevent viral entry by attacking ZIKV E protein. Compounds luteolin, myricetin, astragalin, rutin, (-)-epigallocatechin gallate, carnosine, pedalitin, amongst others, inhibited NS2B-NS3 protease activity which consequently hamper replication. Interestingly, a few NPs had the ability to arrest both viral entry and replication, namely baicalin, (-)-epigallocatechin gallate, curcumin, cephaeline, emetine, and resveratrol. To the best of our knowledge, we obtained only one in vivo study conducted on emetine and results showed that it decreased the levels of circulating ZIKV by approximately 10-fold. Our understanding on NPs exhibiting anti-ZIKV effects in in vivo testing as well as clinical trials is limited. Our trend analysis showed that interest in searching for a cure or prevention against Zika in NPs is negligible and there are no publications yet covering the clinical evaluation. NPs with anti-ZIKV property can a winning strategy in controlling the bio-burden of an epidemic or pandemic. We therefore opine that in the future, more research should be devoted to ZIKV. This review attempts to provide baseline data and roadmap to pursuit detailed investigations for developing potent and novel therapeutic agents to prevent and cure ZIKV infection.